Caso estomatológico - Amorim,José M. S. (2013)
A eight-year-old child presented a painless and well limited swelling in the angle of the jaw. A CT Scan revealed a well defined mass at the level of the jaw left. The histological examination revealed a leiomyoma. The treatment is surgical excision.